Efeito do composto de lixo urbano em um solo arenoso e em plantas de sorgo - Alves, W. L.; Melo, Wanderley José de [UNESP]; Ferreira, M. E. (Sociedade Brasileira de Ciência do Solo, 1999)
A greenhouse experiment was carried out to evaluate the effect of urban waste compost on soil fertility and on total and extracted contents (DTPA 0.005 mol L-1 pH 7.3) of the elements Fe, Mn, Zn and Ni in a sandy Red-Yellow Podzolic soil (Ultisol). The yield of dry matter of Sorghum bicolor plants and the content of P, K, Ca, Mg, Fe, Mn, Zn and Ni were evaluated in plant tops as a function of compost rates of 0, 12.5, 25, 50 and 100 t ha-1, in the absence and presence of mineral fertilizers. Dry matter yield increased with the compost rates only in the absence of mineral fertilization. Ni was not detected in the plant tops of sorghum, whereas Fe, Mn and Zn contents were related with the DTPA-extracted contents of these elements in the soil. The application of urban waste compost increased pH, organic matter, exchangeable bases, P-resin and CEC values of the soil, reducing the potential acidity (H + Al). The total contents of Fe, Mn and Zn in the soil increased with the compost rates, whereas the total Ni content increased only in the absence of mineral fertilization. The contents of Zn and Ni in the soil, extracted with DTPA, increased with the compost rates both in the absence and in the presence of mineral fertilization; Mn and Fe contents, however, decreased in the presence of mineral fertilization and were not affected in its absence. Although accumulation of the heavy metals in the plants was not detected, the content of some elements in the soil increased; therefore, attention should be given to the possibility of soil contamination when conducting successive applications of urban waste compost.

Estudou-se o efeito do composto de lixo urbano na fertilidade e nos teores totais e extraídos com solução de DTPA 0,005 mol L-1 pH 7,3 dos elementos Fe, Mn, Zn e Ni em um Podzólico Vermelho-Amarelo textura arenosa, em casa de vegetação. Empregou-se sorgo como planta-teste, avaliando-se perfilhamento, produção de matéria seca e quantidade acumulada dos elementos P, K, Ca, Mg, Fe, Mn, Zn e Ni em função de doses de composto equivalentes a 0, 12,5, 25, 50 e 100 t ha-1, na ausência e na presença de adubação mineral. O composto aumentou a produção de matéria seca do sorgo na ausência de adubação mineral; esta, contudo, promoveu maior aumento de produção e perfilhamento das plantas. Na parte aérea de sorgo, não foi detectado Ni, enquanto as quantidades acumuladas de Fe, Mn e Zn relacionaram-se com os teores no solo extraídos com DTPA. A aplicação do composto de lixo promoveu aumento dos valores de pH, matéria orgânica, bases trocáveis, P resina e CTC do solo, reduzindo a acidez potencial (H + Al). Os teores totais de Fe, Mn e Zn no solo aumentaram com as doses do composto, enquanto o de Ni aumentou somente na ausência de adubação mineral. Os teores de Zn e Ni no solo, extraídos com DTPA, aumentaram com as doses do composto tanto na ausência como na presença de adubação mineral; já os de Mn e Fe diminuíram na presença de adubação mineral e não foram alterados na sua ausência. Apesar de não ter ocorrido acúmulo dos metais pesados no tecido vegetal, houve incremento no solo de alguns dos elementos; portanto, deve-se atentar para aplicações sucessivas de composto de lixo domiciliar.
Urban waste compost effects on sandy soil and sorghum plants
Keywords: adubação orgânica; DTPA; metais pesados; acidez do solo; organic fertilization; DTPA; heavy metals; MSW; soil acidity